Evaluation of the erosive capacity of children’s beverages on primary teeth enamel: An in vitro study - Tocolini, Daniel-Gheur (J Clin Exp Dent, 2018)
BACKGROUND: The consumption of acidified beverages, associated with lower mineralization of primary enamel, is the ideal combination for the development and progression of dental erosion. The objective of this study is to analyze the erosive capacity and the surface roughness of primary teeth enamel after exposure to three different brands of grape juices. MATERIAL AND METHODS: Forty enamel blocks of primary teeth were obtained, attened and polished. They were submitted to initial surface roughness analysis (baseline), and randomly assigned into four groups (n = 10): NAT: natural grape juice (Campo Largo); IND: industrialized grape juice (Dell Vale Kapo); SOY: soy-based grape juice (Ades); and CONT (control): artificial saliva. Blocks were immersed for 2 min, 3 times per day, for 9 days. During the whole time of the experiment, the enamel blocks were stored in artificial saliva. After the 9 days, the roughness parameters were determined again. The beverages were analyzed for pH and titratable acidity. Data were statistically analyzed (α = 0.05). RESULTS: The surface roughness did not differ significantly among groups (p > 0.05). However, after the immersion in the different grape juices, the surface roughness values increased significantly (p< 0.05). The pH values were weakly correlated to acidity values; NAT showed the highest titratable acidity values than the other juices (p<0.05). CONCLUSIONS: Although the surface roughness values of the experimental groups did not differ from the control group, there was a difference in initial and final roughness in all groups. Grape juices, especially natural, may have an erosive capacity, changing the surface roughness of primary dental enamel. Key words:Dental erosion, beverages, enamel, roughness.